Frictional behaviour of AA7050/B4Cp hybrid composites. (12th September 2019) - Ranjith, R.; Giridharan, P.K.; Subramanian, M.
In this work, AA7050 aluminium alloy reinforced with SiCp was fabricated through the liquid stir casting technique. The influence of % reinforcement, sliding speed, applied load and sliding distance on friction coefficient was investigated using a pin on disc equipment with tests based on the design of experiments. The results revealed that the friction coefficient increases with an increase in % reinforcement. Sliding speed, load and distance follow the similar trend that is at saddle point it registers maximum and after that COF decreases with an increase in any of the above-said parameters. The result showed that the presence of a mechanical mixed layer reduces the coefficient of friction and it's broke down leads to an increase in friction factor. The presence of mechanical mixed layer was confirmed through EDAX analysis. A mathematical model for friction coefficient was developed using response surface methodology and the combined effect of process parameters was thoroughly analysed.